2018
DOI: 10.1016/j.healun.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

The first-in-human experience with a minimally invasive, ambulatory, counterpulsation heart assist system for advanced congestive heart failure

Abstract: This study demonstrates a high rate of successful outcomes with an excellent risk-to-benefit profile. This FIH experience reveals that the iVAS can be successfully inserted in a standardized approach, provide hemodynamic support, can be interrupted for short periods, and allows for ambulation. A multicenter trial to investigate effectiveness and safety is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 13 publications
(16 reference statements)
0
21
0
Order By: Relevance
“…According to the data from the ISHLT registry, approximately 50% of heart transplant recipients are treated with pretransplant MCS (7 studies showed comparable early and long-term outcomes in recipients with pre-transplant temporal MCS (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…According to the data from the ISHLT registry, approximately 50% of heart transplant recipients are treated with pretransplant MCS (7 studies showed comparable early and long-term outcomes in recipients with pre-transplant temporal MCS (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…46 The SID is an electromechanical and pneumatic conduit with a chimney that allows for shuttling of air between the pump and external driver and communication of the captured electrocardiogram (ECG) signals that are transmitted to the driver from three subcutaneous electrodes. 47 In the first in-human trial, 13 out of 14 patients were ambulatory within 24 h and successfully transplanted after. One patient needed escalation of support and received Impella 5.0 then CentriMag blood pump for extracorporeal membrane oxygenation (ECMO) before transplanted.…”
Section: Counter-pulsation Devicesmentioning
confidence: 99%
“…There was no pump thrombosis, stroke, and gastrointestinal bleeding in this single center study. 47 The Kantrowitz CardioVAD (research device, not in clinical use). Another attempt for long-term pulsatile balloon pump is the Kantrowitz CardioVAD (KCV), which utilizes extra-aortic placement and provides partial support for HF patient not qualified for transplant.…”
Section: Counter-pulsation Devicesmentioning
confidence: 99%
“…91 Recently a minimally invasive, transaxillary arterial IABP (Nupulse®, NuPulseCV, Raleigh, NC, USA) has been developed as a durable ambulatory option for bridging counterpulsation therapy. 92 After heart transplantation, exercise capacity improves dramatically compared with endstage heart failure, but this capacity continues to be subnormal compared to age-matched healthy individuals, and peak oxygen uptake ranges from 50-70% of the general healthy population. 93 Some of the factors which may explain this finding include chronotropic incompetence related to autonomic denervation of the transplanted heart, diastolic dysfunction, reduced stroke volume, reduced muscle strength, and reduced oxidative capacity or reduced capillary density.…”
Section: Frailty Modification Through Nutrition and Rehabilitationmentioning
confidence: 99%